Pelatihan Talents Mapping Pada Guru-Guru SMK Negeri 11 Bekasi - Priatna, Wowon; Purnomo, Rakhmat; Fadjriya, Andry; Kustanto, Prio (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
Talents Mapping is an application tool for recognizing one's talents based on 34 talent themes adopted from Gallup's research, so that someone can also find out their personal strength and typology's strength. Talend mapping training is motivated by a request from the leadership of SMK Negeri 11 Bekasi so that teachers can get to know their respective talents so that in teaching and educating students more optimally and teachers after receiving this activity can teach back to their students. This training begins by recording teachers' emails to create a classroom account to ask preliminary aptitude test questions and share material. The training was conducted at the Computer Lab of SMK Negeri 11 on 12 July 2020 with 46 teachers participating. The results of the training for teachers using the lecture method, filling out the instruments, and comments from resource persons. The teachers fill in the questions about themselves at www.temubakat.com, then the answers are mapped using talents mapping to find out the potential talents of each teacher.